Economic Evaluations of Interventions for Transtibial Amputees: A Scoping Review of Comparative Studies. (January 2019) - Highsmith, M. Jason; Kahle, Jason T.; Lewandowski, Amanda; Klenow, Tyler D.; Orriola, John J.; Miro, Rebecca M.; Hill, LTC. Owen T.; Raschke, Sylvia Ursula; Orendurff, Michael S.; Highsmith, James T.; Sutton, Bryce S.
Abstract : ABSTRACT: Transtibial amputation (TTA) is life-altering emotionally, functionally, and economically. The economic impact to all stakeholders is largely unknown, as is the cost-effectiveness of prosthetic intervention. This scoping report's purpose was to determine if there is sufficient evidence to conduct a formal systematic review or meta-analysis in any particular prosthetic intervention area and to determine if any evidence statements could be synthesized relative to economic evaluation of interventions provided to patients with TTA. The scoping review revealed six articles representing three topical areas of transtibial care: Care Models, Prosthetic Treatment, and Prosthetic Sockets. All six articles were cost-identification or cost-consequence design and included a total of 704 subjects. Presently, it can be concluded with moderate confidence that specific weight bearing and total contact sockets for transtibial amputees are functionally and economically equivalent in the short term when costs, delivery time, and all stakeholder perspectives are considered. Long-term socket outcomes are relatively unexplored. Further primary research is needed beyond this to determine cost-effectiveness for other areas of transtibial prosthetic care although clinical outcomes are somewhat established through systematic review and meta-analysis in other areas of care. Conversely, evaluation of narrative economic reports relative to transtibial care may be sufficient to warrant further analysis. Guidance from the profession may also be useful in devising a strategy for how to assure economic analyses are a routine element of future prosthetic science.